PERBANDINGAN PENDEKATAN BELAJAR (LEARNING APPROACHES) MAHASISWA TAHUN PERTAMA DAN TAHUN KETIGA FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Made Indira Dianti Sanjiwani; Ni Putu Wardani; Ni Luh Putu Eka Diarthini; Dewa Ayu Agus Sri Laksemi (E-Jurnal Medika Udayana, 2021)
Learning approach is a method applied by individuals in studying material to achieve learning outcomes. Learning approaches can be classified into surface, deep, and strategic learning approach. Changes in the learning environment may affect the learning process of a student. This is prone to occur in first-year medical students who are experiencing a transition from high school education to university. The purpose of this study was to explore the comparison of the learning approaches used by first and third-year medical students. This study is an analytical study with a cross-sectional approach using the Indonesian version of The Approaches and Study Skills Inventory for Students (ASSIST) questionnaire. The sample collection technique used random sampling method with a sample size of 216 students. The collected data were analyzed in univariate and bivariate ways using a computer program. Respondents ranging from 18 to 22 years old and most of them were females (66.2%). First-year student respondents were 106 people (49.1%) and third-year students were 110 people (50.9%). Comparative analysis for categorical data was carried out using the chi-square test and obtained p-value = 0.011 (p <0.05), indicates that there is a significant difference between the types of learning approaches of first and third-year medical students. Third-year students were found to have a deep learning approach dominantly, while first-year students have a surface learning approach dominantly. Further research related to learning approaches should be carried out as a contribution to the curriculum formation process and may encourage students to adopt a good learning approach